Sisterhood as a means of resisting patriarchy in Mariama Bâ’s So Long a Letter - Fatima Zahra El Arbaoui (Rainbow : Journal of Literature, Linguistics and Culture Studies, 2023)
Space and role restrictions, social disparities, cultural disintegration, and political confrontations are just a few of the difficulties that African women often face. This article aims to show how women negotiate their space within such limitations through female friendship, solidarity, and sisterhood as legitimate tools of female bonding and feasible means for the woman’s educational, political and economic independence in Mariama Bâ’s So Long a Letter. This novel raises concerns about the extent to which the consciousness, or the actual experience of patriarchal abuse in its various shapes, brings women from different socio-economic backgrounds closer together, furnishing them with a device of resistance in a highly antagonistic social environment, and enabling them to appreciate women’s empowerment, and to extend female friendship into female solidarity that participates in nation building.